Aligning Educational Facilities with Curriculum Demands: Insights from Integrated Islamic Primary Schools in West Java - Firmansyah, Rangga; Cardiah, Tita; Golda, Nensi; Asif, Nayeem; Utaberta, Nangkula (Perhimpunan Intelektual Muslim Indonesia, 2024)
The purpose of this study is to investigate the appropriateness and condition of educational facilities in compliance with Ministerial Regulation No. 24 of 2007, as well as the relationship between these facilities and the curriculum at Integrated Islamic Primary Schools (SDIT) in Bandung, West Java. In this study, nine full-day SDITs were reviewed using a qualitative methodology that included snowball sampling. According to the findings, although the majority of schools are able to meet the infrastructure standards, there are disparities in the conditions of the facilities, such as differences in classroom size, ventilation, and library resources, which show that there is a need for changes. Furthermore, the variety of curricular applications, which can range from national to international systems, has a considerable impact on the spatial organisation of school facilities as well as the functional criteria that must be met. It is necessary to have appropriate infrastructure assistance in order to facilitate the integration of various curricular aspects in order to cultivate an effective learning environment that is respectful of Islamic educational ideals. According to the findings of this study, improving facility standards and bringing them into closer alignment with the requirements of a wide variety of curricula can have a considerable positive impact on educational outcomes.